Technological change and the Mexican labor market: The role of tasks - Meza González, Liliana; Rodríguez Pérez, Reyna Elizabeth (Estudios Económicos de El Colegio de México, 2022)
Using data from ENIGH 2000-2014, this paper aims, first, to describe what is happening in the Mexican labor market with regard to the relative demand and supply of workers defined by their occupation, when occupations are classified into non-routine and routine and, within these, into cognitive and manual, based on a thorough analysis of tasks. Second, this paper tries to understand how wages and formality are related to task-biased technological change (TBTC) in Mexico. The analysis differentiates the male and female labor markets.